2018
DOI: 10.1111/vco.12450
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular cyclic adenosine monophosphate‐dependent protein kinase A autoantibody and C‐reactive protein as serum biomarkers for diagnosis of cancer in dogs

Abstract: Protein kinase A, a cyclic adenosine monophosphate (AMP)‐dependent enzyme, normally exists within mammalian cells; however, in cancer cells, it can leak out and be found in the serum. Extracellular cyclic AMP‐dependent protein kinase A (ECPKA) has been determined to increase in the serum of cancer‐bearing dogs. However, there have been no reports in the veterinary literature on serum ECPKA autoantibody (ECPKA‐Ab) expression in dogs with cancer. The aim of this study was to evaluate ECPKA‐Ab and C‐reactive prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The aim of this study was to demonstrate the increase in AniScan ECPKA antibody levels in dogs bearing malignant tumors compared to non-tumor groups and to evaluate the usefulness of this approach for detecting malignant tumors in dogs. A significantly higher ECPKA antibody level was found in various malignant tumor groups than control groups, as shown in previous studies with regard to canine malignant tumors [13,14]. In human medicine, abundant evidence shows that ECPKA activity or the ECPKA autoantibody level increases in various malignant tumors regardless of the type of tumor or location, including bladder, breast, cervical, colon, esophageal, gastric, liver, lung, ovarian, pancreatic, prostate, renal, renal cell, small bowel, rectal, and adenocystic carcinomas; melanoma; sarcoma and thymoma; liposarcoma; and leiomyosarcoma [8].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The aim of this study was to demonstrate the increase in AniScan ECPKA antibody levels in dogs bearing malignant tumors compared to non-tumor groups and to evaluate the usefulness of this approach for detecting malignant tumors in dogs. A significantly higher ECPKA antibody level was found in various malignant tumor groups than control groups, as shown in previous studies with regard to canine malignant tumors [13,14]. In human medicine, abundant evidence shows that ECPKA activity or the ECPKA autoantibody level increases in various malignant tumors regardless of the type of tumor or location, including bladder, breast, cervical, colon, esophageal, gastric, liver, lung, ovarian, pancreatic, prostate, renal, renal cell, small bowel, rectal, and adenocystic carcinomas; melanoma; sarcoma and thymoma; liposarcoma; and leiomyosarcoma [8].…”
Section: Discussionsupporting
confidence: 81%
“…Evidence shows that the activity of ECPKA increases in various malignant tumors in human medicine [8][9][10][11], and a report demonstrated that ECPKA activity decreased after surgical removal in human melanoma patients [12]. However, although it is suggested that the ECPKA level also increases in malignant tumors in mammals other than humans, few studies regarding ECPKA are available in the veterinary literature [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…CRP may also be increased in neoplastic conditions in dogs (Ryu et al . ), but reports on CRP and brain tumours in dogs remain sparse. Our findings of slightly elevated CRP in dogs with brain tumours or inflammatory brain disease only indicate a systemic inflammatory response, but the specific cause was not further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, serum CRP may not increase with brain conditions, unless the blood brain barrier is compromised and a systemic inflammatory response is induced, as for instance in steroid-responsive meningitis-arteritis (Lowrie et al 2009). CRP may also be increased in neoplastic conditions in dogs (Ryu et al 2019), but reports on CRP and brain tumours in dogs remain sparse. Our findings of slightly elevated CRP in dogs with brain tumours or inflammatory brain disease only indicate a systemic inflammatory response, but the specific cause was not further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Wu and colleagues have recently recognized significant differences in PKA catalytic Cα (PKA-Cα) levels between volunteers and gastric cancers, but not colorectal, in sera [22]. Analogous cancer-related findings have also been obtained in canine species [23,24].…”
Section: Introductionmentioning
confidence: 91%